Epidemiology of Persistent Tympanic Membrane Perforations Subsequent to Tympanostomy Tubes Assessed With Real World Data. Issue 9 (October 2016) - Alrwisan, Adel; Winterstein, Almut G.; Antonelli, Patrick J.
Abstract : Objective: To quantify the incidence of persistent tympanic membrane perforation (TMP) after tympanostomy tube (TT) surgery using a large population-based cohort. Study Design: A retrospective cohort study. Setting: Medicaid claims data from 1999 to 2006. Patients: We studied healthy children who had Medicaid eligibility within 6 months of birth that received TTs and had 2 to 7 years of follow-up. Main Outcome Measures: We operationalized persistent TMP by a charge for tympanoplasty and/or one or more diagnoses of TMP. Results: We identified 47, 724 children who received TTs and had ≥2 years eligibility. The incidence of persistent TMP varied, based on definition and follow-up. The 2 and 7-year TMP rates were: 0.38% and 3.81% for two TMP diagnoses 6 months apart or tympanoplasty; 0.26% and 2.94% for two TMP diagnoses 6 months apart; 0.13% and 1.73% for tympanoplasty, alone; 0.04% and 1.21% for tympanoplasty preceded by one TMP diagnosis; and 0.01% and 0.52% for tympanoplasty and two TMP diagnoses 6 months apart. Reinserting TTs was associated with an increased likelihood of persistent TMP (adjusted hazard ratio [HR] = 1.98, 95% CI 1.49–2.63). Each year increase in age was associated with 49% increase in the risk of persistent TMP. Conclusion: Billing claims data may be used to assess the rate of persistent TMP after TT placement in large populations, yielding results consistent with findings from cohort studies and meta-analyses. Our findings may serve as the basis for future TMP research using real world datasets.